The Waiting Time Analysis of Educated Workers in Sumbawa Regency - Siti Maryam, Siti Maryam; Akung Daeng, Akung Daeng; Dwi Saputri, Dwi Saputri (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
The purpose of this study is to analyze the causes and dilemmas of educated workers in Sumbawa Regency to experience waiting times in looking for or finding work in accordance with the demand side hypothesis of wage levels, types of work, education levels. From the supply side namely gender (gender specific), majoring in education, and work experience. This study used a quantitative approach with the type of descriptive research. The population in this study was the educated workforce in Sumbawa Regency with the last education such as Senior high school , D-I / II / III, or S1 and 100 samples were taken. This research data used primary data from questionnaire results. The results of this study indicated that educated workers experience waiting time or unemployed due to the level of education that was not in accordance with the demands of existing jobs or not in accordance with the majors they completed. Educated workers were willing to accept any job if they did not get work for a certain time but still consider the level of wages, type of work, and level of education.